Earnings Management as Moderator of Financial Performance and Firm Value in Indonesian Banks - Sochib, Sochib; Liyundira, Fetri Setyo; Ana, Selvia Roos; Yulianti, Ani (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2026)
This study investigates the moderating role of earnings management in the connection between financial performance and firm value in conventional national commercial banks in Indonesia during 2017–2023, including the coronavirus pandemic period. Financial performance is measured by Return on Assets (ROA), Return on Equity (ROE), and Net Interest Margin (NIM). At the same time, the company's value is represented by the Price-Earnings Ratio (PER), Operating Expenses to Operating Income (OEOI), and Non-Performing Loans (NPL). A purposive sampling method selected 23 conventional banks, generating 161 observations. Data were analyzed using Structural Equation Modeling using Partial Least Squares (PLS-SEM) to examine both direct and moderating effects. The analysis shows that financial performance significantly and negatively affects firm value. However, earnings management does not exert a significant effect and fails to moderate the relationship. These findings indicate a gap between theoretical assumptions and actual market behavior, as firm value tends to increase even as profitability declines. The study concludes that firm value in banking is shaped more by market expectations and government policies than short-term profits. Managers should strengthen communication, apply effective risk management, and focus on sustainable strategies. Future research is encouraged to broaden indicators and incorporate macroeconomic and regulatory variables.